The Role of Aceh Local Parties in The 2024 General Election in Realizing Democratization - Kharisatul Janah; Siti Fatimah; Hajar Salamah Salsabila Hariz (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2023)
Regional head elections are political contests involving multiple pairs of candidates, and the winner of this election is determined by the majority of vote casted to them. Aceh is the only province in Indonesia that allows its citizens to form their own political parties. This study examines the role of local parties in Aceh in the 2024 general election in realizing democratization from a democratic perspective. Such a research is classified as normative juridical Law Research, which is research that uses intermediary legal materials in a broad sense, with an approach to laws, theories, concepts, and cases. The results of this research showed that Aceh local parties played some role in the 2024 General Election in realizing democratization, with 6 local parties planning to participate in the simultaneous elections/elections in 2024. Especially in Aceh, this proved that the juridical aspects of legislation governing local parties were still implemented and that the democratic values of popular sovereignty were still upheld. Nevertheless, their role, existence and accountability were currently declining, giving the national parties greater popularity and demand to the Acehnese community. This was because these local parties no longer had central figures who were able to develop democracy in Aceh.